Exploring 1:1 iPad Integration Practices through a TPACK-in-Practice Lens - Malik, Kristina; Lambert, Judy (International Journal of Educational Technology and Learning, 2020)
The TPACK-in-Practice framework of Jaipal and Figg (2013) provides concrete practices that exemplify successful technology integration of teachers. This framework and mixed methods were used to examine the instructional practices of four teachers in a high school where 1:1 iPad integration had been implemented. Findings revealed that three teachers were successful at exhibiting instructional practices considered essential for effective technology integration. One of the teachers, however, only used technology to improve her productivity and therefore, did not see the value in integrating technology in any substantive way in the classroom. The successful teachers transitioned to more student-centered approaches with iPads being used as cognitive tools rather than for productivity purposes only. They were more accepting of risks and became more confident and apt to experiment with a variety of iPad applications. Successful experiences with iPad integration tended to increase motivation and confidence, which led to more integration experimentation.